The influence of chitin synthesis inhibitors on growth of entomopathogenic fungi in vitro - Anna Sapieha; Ryszard Miętkiewski (Acta Mycologica, 2014)
Beauveria bassiana, Paecilomyces farinosus, Verticillium lecanii, Conidiobolus thnmboides, Erynia pieris, E. radicans were examined on medium to which were added three chitin synthesis inhibitors.